2009
DOI: 10.32607/20758251-2009-1-2-78-80
|View full text |Cite
|
Sign up to set email alerts
|

Relative Comparison of Catalytic Characteristics of human Foamy Virus and hIV-1 Integrases

Abstract: Due to their ability to integrate into the host cell's genome, retroviruses represent an optimal basis for the creation of gene therapy vectors. The integration reaction is carried out by a viral enzyme integrase: thus, a detailed research of this enzyme is required. In this work, the catalytic properties of human foamy virus integrase were studied. This virus belongs to the Retroviridae family. The dissociation constant was determined, together with the kinetics of integrase catalytic activity. The data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…All HIV-1 and PFV integrases carrying an N-terminal His 6 -tag were expressed and purified as previously described 51 . All Ku70 proteins carrying N-terminal GST-tag and GST alone were purified as previously described 49 .…”
Section: Methodsmentioning
confidence: 99%
“…All HIV-1 and PFV integrases carrying an N-terminal His 6 -tag were expressed and purified as previously described 51 . All Ku70 proteins carrying N-terminal GST-tag and GST alone were purified as previously described 49 .…”
Section: Methodsmentioning
confidence: 99%
“…A tetramer consists of asymmetrical dimers, each of those interacts with one terminus of viral DNA and performs its integration into cellular DNA [ 28 ]. The comparative study of the catalytic characteristics of the IN of the human foamy virus and HIV-1 revealed a considerable similarity in the functioning of these two enzymes [ 29 , 30 ].…”
Section: Integrase Structure and Integration Mechanismmentioning
confidence: 99%
“…Recombinant proteins expression and purification: GST-mCer-IN and His 6 -Ku70-tRFP were expressed and purified in the same way as His 6 -IN and GST-Ku70, respectively, as previously described in [ 29 , 30 ]. GST-mCer was produced and purified in the same way as GST-mCer-IN.…”
Section: Methodsmentioning
confidence: 99%